2012 IEEE 20th International Symposium on Field-Programmable Custom Computing Machines 2012
DOI: 10.1109/fccm.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating a Random Forest Classifier: Multi-Core, GP-GPU, or FPGA?

Abstract: Abstract-Random forest classification is a well known machine learning technique that generates classifiers in the form of an ensemble ("forest") of decision trees. The classification of an input sample is determined by the majority classification by the ensemble. Traditional random forest classifiers can be highly effective, but classification using a random forest is memory bound and not typically suitable for acceleration using FPGAs or GP-GPUs due to the need to traverse large, possibly irregular decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(83 citation statements)
references
References 7 publications
0
75
0
1
Order By: Relevance
“…To date, several non-chemogenomic studies have shown that the number of trees in a random forest could be reduced to a certain degree without losing model performance [64][65][66][67][68], and often rule-of-thumb suggestions are made and accepted within the different computational communities, which allow model training without previous parameter optimization. To probe whether parameter optimization might be an advantageous step instead of accepting rule-of-thumb guidelines, we investigated how chemogenomic active learning performance changed when reducing the number of trees.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several non-chemogenomic studies have shown that the number of trees in a random forest could be reduced to a certain degree without losing model performance [64][65][66][67][68], and often rule-of-thumb suggestions are made and accepted within the different computational communities, which allow model training without previous parameter optimization. To probe whether parameter optimization might be an advantageous step instead of accepting rule-of-thumb guidelines, we investigated how chemogenomic active learning performance changed when reducing the number of trees.…”
Section: Discussionmentioning
confidence: 99%
“…Our implementation of the random forest classifier uses the version provided by the Weka machine learning library 5 [16], which is a collection of algorithms for machine learning and data mining. We chose the random forest approach, because it is fast and achieves good results [49]. It is important to point out that for this step, another classification algorithm can also be used.…”
Section: Multi-class Global-feature-based Eirmentioning
confidence: 99%
“…It is notable that in most systems this design will be I/O It is notable that all tested software implementations were single threaded, but decision tree ensembles can be effectively implemented as multithreaded programs running on multicore processors [17].…”
Section: Resource Usagementioning
confidence: 99%
“…Parallel implementations of random forests for URL classification on multicore CPU, GPGPU and FPGA are presented in [17]. Publicly available dataset is used by the au- …”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation